Neuroimaging Neurobiology, Multimodal and Network Applications - Zhou, Yongxia (IntechOpen, 2020)
In vivo brain neuroimaging with cutting-edge technologies has achieved great success with high spatial and temporal resolutions. Several distinct medical imaging perspectives such as disease neurobiology, multimodal imaging techniques and applications, large-size clinical trials of neuro-oncology, and bioinformatics with illustrative examples and comprehensive summaries could expand our knowledge of neuroimaging mechanism, methodologies, and applications. This book highlights the possibility and achievement of early detection and multiple neuroimaging biomarkers based on various features for pathophysiological probing and therapeutic prevention. It examines the use of neuroimaging techniques such as magnetic resonance imaging (MRI), electroencephalography (EEG), and near-infrared resonance spectroscopy (NIRS) with specific and innovative biomedical applications. It provides thorough reviews, accurate descriptions, and confirmative evidences of many related important research topics together with up-to-date imaging network management.